Challenges in assessing bone health in early infancy: a narrative review of existing technologies - Pepe, Giorgia; Morabito, Letteria Anna; Corica, Domenico; Aversa, Tommaso; Beretta, Virginia; Scarpa, Elena; Petrolini, Chiara; Dall’Asta, Andrea; Grassi, Federica; Shulhai, Anna-Mariia; Papini, Anna Maria; Albertini, Maria Cristina; et al. (Frontiers in Endocrinology, 2025)
To date, no shared guidelines have been approved for the diagnosis and management of low bone mineral density (BMD), especially in early infancy. Therefore, there is an increasing demand for new methodologies to allow the assessment of bone health status in this specific cohort, which is exposed to several risk factors (e.g. maternal vitamin D deficiency, pregnancy-associated diseases, preterm birth and comorbidities, low birth weight, intrauterine growth restriction). Currently, the assessment of BMD in newborn and infants relies mainly on serum and urinary biochemical markers, in association with several technologies to measure bone mineral content, such as dual-energy X-ray absorptiometry (DXA) and quantitative ultrasound (QUS) being traditionally used, despite many limitations. More recently, Radiofrequency Echographic Multi-Spectrometry (REMS) emerged as a promising tool in clinical practice for screening and monitoring BMD. Due to the radiation-free technology, an extremely ease of use, low costs, an excellent degree of sensitivity, specificity, and reproducibility, REMS technology has proven to be the gold standard technique in sensitive populations such as pregnant women, newborns and infants, allowing mass extended screening strategies. However, to date no validate cut-off reference for REMS in paediatric age are available. Future longitudinal studies on REMS methodology are needed to build reference standards and new shared algorithms, combining biochemical and instrumental data, for the diagnosis, management and treatment of decreased BMD before and after birth.